Awareness of Keratoconus Among the Diagnosed Cases of Keratoconus in Patients Visiting Al Shifa Trust Eye Hospital: Awareness of Keratoconus in Patients - Ahmed, Talia; Akhtar, Farah; Moqeet, Muhammad Abdul; Shah, Hirra Ghaffar; Bukhari, Syeda Filzah; Younas, Nabila (Pakistan Journal of Health Sciences, 2025)
Keratoconus is a chronic, progressive, non-inflammatory, usually bilateral corneal disorder that causes stromal thinning that leads to corneal apical protrusion, irregular astigmatism, and decreased vision. Its etiology is multifactorial, and it is important to determine its awareness and its association with non-genetic, environmental risk factors to prevent it. Objectives: To determine the level of awareness of keratoconus among the diagnosed cases of keratoconus. Methods: This descriptive cross-sectional study was conducted at Al Shifa Trust Eye Hospital in five months using a consecutive sampling technique. SPSS version 22.0 was used for Data Analysis. The Pearson’s Chi-square test was utilized for cross-tabulation. Results: Out of 135 patients, it was seen that participants with a higher level of education (P value 0.0029) and those with positive family history had overall better knowledge about the disease and specific knowledge about eye rubbing as an aggravating factor of the disease (P value 0.00249). In conclusion, overall, 48.1% % had poor knowledge, 34.8% had fair, and only 17% had good knowledge regarding the disease. Conclusions: Despite keratoconus being more common in younger individuals who have internet access, patients still had poor knowledge of the disease. Different strategies can be devised to increase awareness and prevent its progression by eliminating the non-genetic, environmental risk factors, such as eye rubbing and discussing compliance regarding the use of topical anti-allergic medications and regular follow-up visits.